Philippine Economic Update, August 2014 : Investing in the Future, Sharing Growth and Job Opportunities for All - World Bank Group (Washington, DC, 2014)
After recording strong growth in the last two years, Philippine economic growth decelerated to 5.7 percent in the first quarter of 2014 (Q1 2014). After many years of slow poverty reduction, poverty incidence declined by 3 percentage points (PPT) between 2012 and 2013 to 24.9 percent, uplifting 2.5 million Filipinos out of poverty. Given the slow start in Q1 2014, lower government spending in second quarter of 2014 (Q2 2014), and monetary policy tightening, baseline growth projections is revised downwards from 6.6 to 6.4 percent for 2014 and from 6.9 to 6.7 percent for 2015. Strong liquidity and credit growth, as well as higher food and energy prices, continue to exert some risks to price and financial stability. In the medium-term, growth can be sustained and made more inclusive by pursuing structural reforms and investing more in human and physical capital. The Aquino administration has successfully raised tax effort by 1.2 PPT of gross domestic product (GDP) in the last 3 years through the sin tax reform, improved tax administration, and higher growth. These reforms can help the country become more competitive, and in the process create more and better jobs, and accelerate poverty reduction. The Philippine economic update provides an update on key economic and social developments as well as policies over the past 6 months. It also presents findings from recent World Bank studies on the Philippines.